Conductive paste for electrodes of all-solid-state secondary batteries

The conductive material paste with a specific polymer blend improves dispersibility and electrical contact in all-solid-state secondary batteries, addressing internal resistance and high-temperature cycle challenges, enhancing battery performance.

JP7654978B2Active Publication Date: 2025-04-02ZEON CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020563014
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-12-05
Publication Date
2025-04-02
Estimated Expiration
2039-12-05

AI Technical Summary

Technical Problem

Existing all-solid-state secondary batteries face challenges in reducing internal resistance and improving high-temperature cycle characteristics, limiting their application in various temperature ranges.

Method used

A conductive material paste for all-solid-state secondary battery electrodes is developed, comprising a specific polymer blend with (meth)acrylic acid ester monomer units and a solubility parameter of 6.4 (cal/cm³)¹⁄₂ to 10.0 (cal/cm³)¹⁄₂, which enhances dispersibility and electrical contact between electrode active materials, thereby reducing internal resistance and improving high-temperature cycle characteristics.

Benefits of technology

The conductive material paste significantly reduces internal resistance and enhances high-temperature cycle characteristics in all-solid-state secondary batteries, making them more suitable for diverse applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654978000001
    Figure 0007654978000001
Patent Text Reader

Abstract

The present invention aims to provide a conductive material paste for electrodes of all-solid-state secondary batteries, which can provide sufficiently reduced internal resistance and excellent high-temperature cycle characteristics in all-solid-state secondary batteries. The present invention relates to a conductive material, a polymer containing 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units, and a polymer having a solubility parameter (SP value) of 6.4 (cal / cm -3 ) 1 / 2 More than 10.0(cal / cm -3 ) 1 / 2 The conductive material paste for an electrode of an all-solid-state secondary battery contains the following organic solvent:
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive material paste for an all-solid-state secondary battery electrode, a slurry composition for an all-solid-state secondary battery electrode, an electrode for an all-solid-state secondary battery, and an all-solid-state secondary battery. [Background technology]

[0002] In recent years, the demand for secondary batteries such as lithium-ion secondary batteries has been increasing for various applications, including portable terminals such as portable information terminals and portable electronic devices, as well as small home power storage devices, motorcycles, electric vehicles, hybrid electric vehicles, etc. As the applications expand, further improvements in the safety of secondary batteries are required.

[0003] In view of this, all-solid-state secondary batteries that use solid electrolytes instead of organic solvent electrolytes, which are highly flammable and have a high risk of ignition in the event of leakage, have been attracting attention as safe secondary batteries.

[0004] Here, the all-solid-state secondary battery has a solid electrolyte layer between a positive electrode and a negative electrode. The electrodes (positive electrode, negative electrode) can be formed by applying a slurry composition containing an electrode active material (positive electrode active material, negative electrode active material), a binder, a solid electrolyte, etc., onto a current collector, drying the composition, and providing an electrode mixture layer (positive electrode mixture layer, negative electrode mixture layer) on the current collector, and the solid electrolyte layer can be formed by applying a slurry composition containing a binder, a solid electrolyte, etc., onto an electrode or a release substrate, and drying the composition. The all-solid-state secondary battery is generally produced by stacking a positive electrode and a negative electrode so that the positive electrode mixture layer of the positive electrode and the negative electrode mixture layer of the negative electrode face each other via a solid electrolyte layer, and then by pressing.

[0005] In recent years, various studies have been conducted on this process in order to improve the performance of all-solid-state secondary batteries. Patent Document 1 proposes dividing the manufacturing process of the positive electrode composite slurry into a first step of mixing a conductive material and a sulfide inorganic solid electrolyte to obtain a mixture, and a second step of mixing at least the positive electrode active material, the inorganic solid electrolyte, and the above mixture, and reducing the battery resistance at low battery capacity by applying a larger energy in the first step. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-147158 A Summary of the Invention [Problem to be solved by the invention]

[0007] Patent Document 1 is a technology that focuses on reducing the battery resistance at low battery capacity. In all-solid-state secondary batteries, improving cycle characteristics is also a major issue, and in order to expand the possibilities for use in various applications, there is a demand for improving cycle characteristics, particularly in high temperature ranges (high-temperature cycle characteristics).

[0008] An object of the present invention is to provide a conductive material paste for an electrode of an all-solid-state secondary battery, which can provide an all-solid-state secondary battery having sufficiently reduced internal resistance and excellent high-temperature cycle characteristics. [Means for solving the problem]

[0009] The present inventors have discovered that when a slurry composition for an all-solid-state secondary battery electrode is prepared using a paste in which a conductive material, a specific binder, and a specific organic solvent are previously blended, and this slurry composition is used to produce an electrode for an all-solid-state secondary battery, an all-solid-state secondary battery including this electrode can achieve sufficiently reduced internal resistance and excellent high-temperature cycle characteristics, and have completed the present invention.

[0010] That is, the present invention relates to a conductive material, a polymer containing 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units, and a polymer having a solubility parameter (SP value) of 6.4 (cal / cm 3 ) 1 / 2 More than 10.0(cal / cm 3 ) 1 / 2 The present invention relates to a conductive material paste for an electrode of an all-solid-state secondary battery, comprising the following organic solvent:

[0011] In this specification, the term "conductive material paste for an all-solid-state secondary battery electrode" refers to a material used in producing a slurry composition for an all-solid-state secondary battery electrode, and means a composition containing a conductive material, a binder, and an organic solvent. In this specification, "(meth)acrylic" means "acrylic and / or methacrylic". In this specification, "monomer unit" means "structural unit derived from that monomer." Furthermore, "containing a monomer unit" means "a polymer obtained by using that monomer contains a structural unit derived from the monomer," and the content of the monomer unit is expressed as a percentage relative to 100% by mass of the entire polymer. In this specification, the term "solubility parameter (SP value)" refers to the Hansen solubility parameter (δ) (unit: (cal / cm 3 ) 1 / 2 ) and "δ 2 = δd 2 + δp 2 + δh 2In the above equation, "δd" indicates the "contribution term due to intermolecular dispersion forces", "δp" indicates the "contribution term due to intermolecular polar interactions", and "δh" indicates the "contribution term due to intermolecular hydrogen bonds", and each is a physical property value depending on the substance type (see Charles M. Hansen, "Hansen Solubility Parameters: A User's Handbook, Second Edition", CRC Press, Boca Raton FL, (2007) (hereinafter referred to as the "Handbook"). For organic solvents not listed in the Handbook, etc., estimated values ​​calculated using the computer software Hansen Solubility Parameters in Practice (HSPiP) can be used.

[0012] The mechanism by which the conductive paste for an all-solid-state secondary battery electrode of the present invention provides sufficiently reduced internal resistance and excellent high-temperature cycle characteristics in an all-solid-state secondary battery is not clear, but can be presumed as follows. The conductive material paste for an all-solid-state secondary battery electrode of the present invention has excellent dispersibility of the conductive material. Therefore, by using this conductive material paste to prepare a slurry composition for an all-solid-state secondary battery electrode, the conductive material is well dispersed in the slurry composition, and excellent dispersibility in the solid electrolyte and the electrode active material is imparted to the slurry composition. Then, in the electrode mixture layer formed using this slurry composition, uneven distribution of the conductive material is suppressed, and electrical contact between the electrode active materials is sufficiently ensured. Then, by using an electrode having this electrode mixture layer in an all-solid-state secondary battery, it is possible to realize a sufficiently reduced internal resistance and excellent high-temperature cycle characteristics in the all-solid-state secondary battery.

[0013] In the conductive material paste for an all-solid-state secondary battery electrode of the present invention, it is preferable to use a polymer further containing an α,β-unsaturated nitrile monomer unit. By using a polymer further containing an α,β-unsaturated nitrile monomer unit as a binder, the dispersibility of the conductive material in the conductive material paste can be further improved, and a sufficiently reduced internal resistance can be effectively achieved in the all-solid-state secondary battery. In the conductive material paste for an all-solid-state secondary battery electrode of the present invention, it is more preferable to use a polymer containing 2% by mass or more and 30% by mass or less of α,β-unsaturated nitrile monomer units.

[0014] In the conductive paste for an all-solid-state secondary battery electrode of the present invention, it is preferable to use a polymer further containing a hydrophobic monomer unit. In this specification, the term "hydrophobic monomer unit" means "a monomer unit other than the (meth)acrylic acid ester monomer unit and the α,β-unsaturated nitrile monomer unit, the solubility of which in water (25° C.) is 1 g / 1 L or less." By using a polymer further containing a hydrophobic monomer unit as a binder, the dispersibility of the conductive material in the conductive paste can be further improved, and a sufficiently reduced internal resistance can be effectively achieved in the all-solid-state secondary battery. In the conductive paste for an all-solid-state secondary battery electrode of the present invention, it is more preferable to use a polymer containing 3% by mass or more and 60% by mass or less of a hydrophobic monomer unit.

[0015] The present invention relates to a slurry composition for an all-solid-state secondary battery electrode, comprising any one of the conductive pastes, an electrode active material, and a solid electrolyte. The slurry composition for an all-solid-state secondary battery electrode of the present invention can provide an all-solid-state secondary battery with sufficiently reduced internal resistance and excellent high-temperature cycle characteristics.

[0016] The present invention relates to an electrode for an all-solid-state secondary battery, comprising an electrode mixture layer formed using any one of the above-mentioned slurry compositions for an all-solid-state secondary battery. The electrode for an all-solid-state secondary battery of the present invention can provide an all-solid-state secondary battery with sufficiently reduced internal resistance and excellent high-temperature cycle characteristics.

[0017] The present invention relates to an all-solid-state secondary battery comprising the above-mentioned electrode. The all-solid-state secondary battery of the present invention has sufficiently reduced internal resistance and excellent high-temperature cycle characteristics. Effect of the Invention

[0018] According to the present invention, there is provided a conductive material paste for an electrode of an all-solid-state secondary battery, which can bring about sufficiently reduced internal resistance and excellent high-temperature cycle characteristics in an all-solid-state secondary battery. According to the present invention, there are provided a slurry composition for an all-solid-state secondary battery electrode and an electrode for an all-solid-state secondary battery, which can provide an all-solid-state secondary battery with sufficiently reduced internal resistance and excellent high-temperature cycle characteristics. The all-solid-state secondary battery of the present invention has sufficiently reduced internal resistance and excellent high-temperature cycle characteristics, and is highly useful industrially. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described in detail. The conductive material paste for an all-solid-state secondary battery electrode of the present invention is used as a material for preparing a slurry composition for an all-solid-state secondary battery electrode. The slurry composition for all-solid-state secondary battery electrodes of the present invention is used when forming electrode mixture layers (positive electrode mixture layer, negative electrode mixture layer) of an all-solid-state secondary battery. The electrodes for all-solid-state secondary batteries (positive electrode, negative electrode) of the present invention are provided with the electrode mixture layers (positive electrode mixture layer, negative electrode mixture layer) and are used in the manufacture of all-solid-state secondary batteries. In the all-solid-state secondary battery of the present invention, at least one of the positive electrode and the negative electrode is the electrode for the all-solid-state secondary battery of the present invention (positive electrode, negative electrode).

[0020] (Conductive paste for electrodes in all-solid-state secondary batteries) The conductive material paste for an all-solid-state secondary battery electrode of the present invention (hereinafter also referred to as "conductive material paste") comprises a conductive material, a polymer containing 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units (hereinafter also referred to as "(meth)acrylic polymer"), and a solubility parameter (SP value) of 6.4 (cal / cm 3 ) 1 / 2 More than 10.0(cal / cm 3 ) 1 / 2 The conductive paste generally does not contain a solid electrolyte or an electrode active material.

[0021] <Conductive material> The conductive material paste of the present invention contains a conductive material. The conductive material is a component for ensuring electrical contact between electrode active materials in the electrode mixture layer of the all-solid-state secondary battery. Examples of the conductive material include carbon black (e.g., acetylene black, Ketjen Black (registered trademark), furnace black, etc.), single-layer or multi-layer carbon nanotubes (multi-layer carbon nanotubes include cup-stack type), carbon nanohorns, vapor-grown carbon fibers, milled carbon fibers obtained by crushing polymer fibers after firing, single-layer or multi-layer graphene, conductive carbon materials such as carbon nonwoven fabric sheets obtained by firing nonwoven fabric made of polymer fibers, and fibers or foils of various metals. Among them, acetylene black, Ketjen black, and furnace black are preferred. The conductive material can be one type or a combination of two or more types at any ratio.

[0022] <(Meth)acrylic polymer> The conductive paste of the present invention contains a polymer containing 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units. The polymer ((meth)acrylic polymer) containing 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units in the present invention is a binder component. The binder component is a component that binds together components such as the electrode active material contained in the electrode mixture layer and holds them so that they do not fall off from the mixture layer. The (meth)acrylic acid ester polymer may be one type or a combination of two or more types in any ratio.

[0023] Examples of the (meth)acrylic acid ester monomer in the (meth)acrylic acid ester monomer unit include acrylic acid alkyl esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, stearyl acrylate, and 2-ethylhexyl acrylate; acrylic acid alkoxy esters such as 2-methoxyethyl acrylate and 2-ethoxyethyl acrylate; 2-(perfluoroalkyl)ethyl acrylates such as 2-(perfluorobutyl)ethyl acrylate and 2-(perfluoropentyl)ethyl acrylate; and methyl methacrylate. methacrylic acid alkyl esters such as ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, tridecyl methacrylate, n-tetradecyl methacrylate, stearyl methacrylate, and 2-ethylhexyl methacrylate; methacrylic acid alkoxy esters such as 2-methoxyethyl methacrylate and 2-ethoxyethyl methacrylate; 2-(perfluoroalkyl)ethyl methacrylates such as 2-(perfluorobutyl)ethyl methacrylate and 2-(perfluoropentyl)ethyl methacrylate; benzyl acrylate; and the like. The (meth)acrylic acid ester monomer also includes a diester of an α,β-ethylenically unsaturated dicarboxylic acid, and examples thereof include lower alkyl diesters of itaconic acid such as diethyl itaconate and dibutyl itaconate. Among these, methyl acrylate, ethyl acrylate, methyl methacrylate, 2-ethylhexyl acrylate, n-butyl acrylate, t-butyl acrylate, and dibutyl itaconate are preferred, and ethyl acrylate, n-butyl acrylate, and t-butyl acrylate are more preferred.These may be one type or a combination of two or more types in any ratio.

[0024] The content of (meth)acrylic acid ester monomer units in the (meth)acrylic polymer is 25% by mass or more, preferably 30% by mass or more, more preferably 35% by mass, and 95% by mass or less, preferably 90% by mass or less, more preferably 85% by mass or less. If it is equal to or more than the lower limit, it is possible to impart excellent dispersibility in solid electrolytes and the like to a slurry composition using the conductive material paste, and it is possible to sufficiently improve high-temperature cycle characteristics. If it is equal to or less than the upper limit, the dispersibility of the conductive material in the conductive material paste is sufficient, and it is possible to sufficiently reduce internal resistance.

[0025] In the present invention, it is important that the (meth)acrylic polymer contains 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units. As long as this requirement is satisfied, the type and content of monomer units other than the (meth)acrylic acid ester monomer units can be arbitrary.

[0026] The (meth)acrylic polymer preferably contains an α,β-unsaturated nitrile monomer. Examples of the α,β-unsaturated nitrile monomer include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, and α-ethylacrylonitrile. Among these, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. The α,β-unsaturated nitrile monomer may be one type or a combination of two or more types in any ratio.

[0027] The content of the α,β-unsaturated nitrile monomer unit is preferably 2% by mass or more, more preferably 3% by mass or more, particularly preferably 4% by mass, and is preferably 30% by mass or less, more preferably 28% by mass or less, and even more preferably 26% by mass or less. If it is equal to or more than the lower limit, the dispersibility of the conductive material in the conductive material paste can be further improved, and the internal resistance can be effectively reduced. If it is equal to or less than the upper limit, the polymer is easily dissolved in an organic solvent, which is advantageous in improving cycle characteristics.

[0028] The (meth)acrylic polymer may further contain a hydrophobic monomer unit. Examples of the hydrophobic monomer unit include an aromatic vinyl monomer unit, a conjugated diene monomer unit, and an olefin monomer unit. The hydrophobic monomer unit does not include a (meth)acrylic acid ester monomer unit or an α,β-unsaturated nitrile monomer. The hydrophobic monomer unit may be one type or a combination of two or more types in any ratio.

[0029] Examples of the aromatic vinyl monomer include aromatic vinyl monomers such as styrene, chlorostyrene, vinyltoluene, t-butylstyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene, α-methylstyrene, and divinylbenzene. Among these, styrene and vinylnaphthalene are preferred. Examples of the conjugated diene monomer include conjugated diene compounds having 4 or more carbon atoms, such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, etc. Among these, 1,3-butadiene and isoprene are preferred. Examples of the olefin monomer include 1-olefin monomers, and examples of the 1-olefin include ethylene, propylene, and 1-butene, with ethylene being preferred. The olefin monomer unit may be a structural unit (conjugated diene hydride unit) obtained by hydrogenating a conjugated diene monomer unit, and among these, a 1,3-butadiene monomer unit, a 1,3-butadiene hydride unit, which is a structural unit obtained by hydrogenating an isoprene monomer unit, and an isoprene hydride unit are preferred.

[0030] From the viewpoints of dispersibility of the conductive material in the conductive paste and reduction of internal resistance, the content of the hydrophobic monomer unit is preferably 3 mass% or more, more preferably 10 mass% or more, even more preferably 12 mass% or more, particularly preferably 14 mass% or more, and is preferably 60 mass% or less, more preferably 55 mass% or less, even more preferably 50 mass% or less, particularly preferably 45 mass% or less.

[0031] The (meth)acrylic polymer may contain other monomer units other than the above-mentioned various monomer units. Examples of other monomer units include unsaturated carboxylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, and fumaric acid; amide monomers such as acrylamide, N-methylolacrylamide, and acrylamido-2-methylpropanesulfonic acid; halogen atom-containing monomers such as vinyl chloride and vinylidene chloride; vinyl ester monomers such as vinyl acetate, vinyl propionate, vinyl butyrate, and vinyl benzoate; vinyl ether monomers such as methyl vinyl ether, ethyl vinyl ether, and butyl vinyl ether; vinyl ketone monomers such as methyl vinyl ketone, ethyl vinyl ketone, butyl vinyl ketone, hexyl vinyl ketone, and isopropenyl vinyl ketone; heterocyclic ring-containing vinyl monomers such as N-vinylpyrrolidone, vinylpyridine, and vinylimidazole; glycidyl group-containing monomers such as glycidyl acrylate, glycidyl methacrylate, and allyl glycidyl ether; and the like. These may be one or a combination of two or more in any ratio.

[0032] A polyfunctional monomer having two or more polymerization reactive groups increases the gel amount of the polymer, so the content is preferably 1% by mass or less, and it is particularly preferable that the polymer is substantially free of such a polyfunctional monomer.

[0033] The (meth)acrylic polymer may be composed of 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units and one or more selected from α,β-unsaturated nitrile monomer units, hydrophobic monomer units, and other monomers. The suitable amounts and types of the α,β-unsaturated nitrile monomer units, hydrophobic monomer units, and other monomers are as described above.

[0034] The weight average molecular weight of the (meth)acrylic polymer is preferably 50,000 or more, more preferably 100,000 or more, from the viewpoint of slurry storage stability, and is preferably 5,000,000 or less, more preferably 2,000,000 or less, from the viewpoint of slurry dispersibility. In this specification, the "weight average molecular weight" can be measured by the method described in the Examples section of this specification.

[0035] The gel content of the (meth)acrylic polymer is preferably 50% by mass or less, more preferably 10% by mass or less, and particularly preferably 0%. If it is less than the upper limit, excellent dispersibility in electrode active materials and solid electrolytes can be imparted to a slurry composition using the conductive paste. The gel content can be controlled by the type and amount of monomer in the polymer, the type and amount of chain transfer agent used during polymerization, polymerization temperature, etc. In this specification, the "gel amount" refers to a value measured by the method described in the Examples section of this specification.

[0036] The method for preparing the (meth)acrylic polymer is not particularly limited, and the (meth)acrylic polymer can be obtained by polymerizing a monomer composition containing the above-mentioned monomers. The content ratio of each monomer in the monomer composition can be determined based on the content ratio of each monomer unit in the polymer. The polymerization method is not particularly limited, and examples thereof include solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization. In each polymerization method, an emulsifier, a polymerization initiator, and the like can be used as necessary. The olefin monomer unit can be introduced by hydrogenating the conjugated diene monomer unit. The hydrogenation method is not particularly limited, and a known method can be used.

[0037] <Organic solvent> The conductive paste of the present invention has a solubility parameter (SP value) of 6.4 (cal / cm 3 ) 1 / 2 More than 10.0(cal / cm 3 ) 1 / 2 The following organic solvents are included:

[0038] The solubility parameter (SP value) of the organic solvent is 6.5 (cal / cm 3 ) 1 / 2 More than 7.5 (cal / cm 3 ) 1 / 2 More preferably, 8.0 (cal / cm 3 ) 1 / 2 More preferably, 9.8 (cal / cm 3 ) 1 / 2 Less than 9.5 (cal / cm 3 ) 1 / 2 Less than 9.0 (cal / cm 3 ) 1 / 2 The following is even more preferred:

[0039] Examples of organic solvents include toluene (8.9), xylene (8.5), cyclopentyl methyl ether (CPME) (8.4), butyl butyrate (8.1), dibutyl ether (7.4), hexane (7.3), and decane (6.5). The numbers in parentheses are the solubility parameters (SP values) (unit: cal / cm 3 ) 1 / 2 Of these, xylene and butyl butyrate are preferred from the viewpoint of affinity with the solid electrolyte. The organic solvent may be one type or a combination of two or more types in any ratio.

[0040] <Other ingredients> The conductive paste of the present invention may contain, in addition to the above components, components such as a leveling agent, a reinforcing agent, an antifoaming agent, an antiaging agent, a surfactant, and a dispersant. Known components can be used as these components. In addition, as long as the effects of the present invention are not impaired, a binder component other than a (meth)acrylic polymer may be contained. For example, a polymer containing a monomer unit selected from vinylidene fluoride (VDF) monomer units and hexafluoropropylene (HFP) monomer units (e.g., polyvinylidene fluoride (PVDF), poly(hexafluoropropylene) (PHFP)), etc.), a styrene-butadiene copolymer (SBR), an acrylonitrile-butadiene copolymer (NBR), and hydrogenated NBR may be included. In addition, as long as the effects of the present invention are not impaired, a binder component having a solubility parameter (SP value) of 6.4 (cal / cm 3 ) 1 / 2 More than 10.0(cal / cm 3 ) 1 / 2 The solvent may contain solvents other than the following organic solvents.

[0041] <Conductive paste composition and viscosity> The solid content concentration of the conductive material paste is preferably 5% by mass or more, more preferably 7% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less. The amount of the conductive material per 100 parts by mass of the solid content of the conductive material paste can be more than 10 parts by mass and can be 95 parts by mass or less.

[0042] The viscosity of the conductive paste of the present invention (Brookfield B type viscometer, 60 rpm, 25° C.) is preferably less than 5000 mPa·s, more preferably less than 3000 mPa·s. From the viewpoint of stability over time, the viscosity is preferably 500 mPa·s or more, more preferably 1000 mPa·s or more.

[0043] <Preparation method of conductive paste> The method for preparing the conductive paste of the present invention is not particularly limited, and examples thereof include a method in which the above-mentioned conductive material, the (meth)acrylic polymer and any other components are mixed in an organic solvent. When the (meth)acrylic polymer is obtained as an aqueous dispersion, the solvent of the aqueous dispersion is exchanged with the organic solvent, and the conductive material and other components are mixed before or after the solvent exchange to obtain a conductive material paste. The method of solvent exchange is not particularly limited, and examples thereof include a method in which the aqueous dispersion and the organic solvent are placed in a rotary evaporator, and the solvent exchange and dehydration are performed at a predetermined temperature under reduced pressure. The conductive material is preferably mixed after replacing the (meth)acrylic polymer with an organic solvent. In order to adjust the concentration of the conductive material paste, an organic solvent may be further added after the solvent exchange or after mixing the conductive material.

[0044] (Slurry composition for electrodes of all-solid secondary batteries) The slurry composition for an all-solid-state secondary battery electrode of the present invention (hereinafter also referred to as "slurry composition") contains the conductive material paste for an all-solid-state secondary battery electrode of the present invention, a solid electrolyte, and an electrode active material.

[0045] <Solid electrolyte> The solid electrolyte is not particularly limited as long as it has the conductivity of charge carriers such as lithium ions, and examples of the solid electrolyte include inorganic solid electrolytes and polymer inorganic solid electrolytes. The solid electrolyte may be one type or a combination of two or more types in any ratio, and may be a mixture of an inorganic solid electrolyte and a polymer inorganic solid electrolyte.

[0046] <<Inorganic solid electrolyte>> The inorganic solid electrolyte is not particularly limited, and examples thereof include crystalline inorganic ion conductors and amorphous inorganic ion conductors. For example, when the all-solid-state secondary battery is an all-solid-state lithium ion secondary battery, the inorganic solid electrolyte is preferably a crystalline inorganic lithium ion conductor or an amorphous inorganic lithium ion conductor.

[0047] Hereinafter, a case will be described in which the all-solid-state secondary battery is an all-solid-state lithium ion secondary battery as an example, but the present invention is not limited to this case. Crystalline inorganic lithium ion conductors include Li3N, LISICON (Li 14 Zn(GeO4)4), perovskite-type Li 0.5 La0.5 TiO3, garnet type Li7La3Zr2O 10 , LIPON (Li 3+y PO 4-x N x ), Thio-LISICON (Li 3.75 Ge 0.25 P 0.75 S4) and the like. Examples of amorphous inorganic lithium ion conductors include glass Li-Si-SO and Li-PS.

[0048] Among these, from the viewpoint of the electrical conductivity of the inorganic solid electrolyte, an amorphous inorganic lithium ion conductor is preferred, and an amorphous sulfide containing Li and P is more preferred because it has high lithium ion conductivity and can reduce internal resistance.

[0049] The amorphous sulfide containing Li and P is more preferably a sulfide glass made of Li2S and P2S5 from the viewpoint of reducing the internal resistance of the battery and improving the output characteristics, and particularly preferably a sulfide glass made from a mixed raw material of Li2S and P2S5 having a molar ratio of Li2S:P2S5 of 65:35 to 85:15. Sulfide glass ceramics obtained by reacting such a mixed raw material by a mechanochemical method can also be suitably used. From the viewpoint of maintaining a high lithium ion conductivity, the mixed raw material preferably has a molar ratio of Li2S:P2S5 of 68:32 to 80:20.

[0050] The lithium ion conductivity of the inorganic solid electrolyte is not particularly limited and is not more than 1×10 -4 S / cm or more is preferable, and 1×10 -3 More preferably, it is S / cm or more.

[0051] The amorphous sulfide inorganic solid electrolyte containing Li and P can contain at least one sulfide selected from the group consisting of Al2S3, B2S3 and SiS2 as a starting material in addition to the above Li2S and P2S5 to the extent that the ion conductivity is not reduced. This can stabilize the glass component in the inorganic solid electrolyte. Similarly, the inorganic solid electrolyte may contain at least one lithium ortho-oxo acid selected from the group consisting of Li3PO4, Li4SiO4, Li4GeO4, Li3BO3, and Li3AlO3, in addition to Li2S and P2S5, which can stabilize the glass component in the inorganic solid electrolyte.

[0052] The number-average particle size of the inorganic solid electrolyte is preferably 0.1 μm or more, more preferably 0.3 μm or more, and is preferably 20 μm or less, more preferably 10 μm or less, even more preferably 7 μm or less, and even more preferably 5 μm or less. If it is equal to or greater than the lower limit, handling is easy and the adhesiveness of the electrode mixture layer formed using the slurry composition can be sufficiently increased. On the other hand, if it is equal to or less than the upper limit, the surface area of ​​the inorganic solid electrolyte can be sufficiently secured, and the output characteristics of the all-solid-state secondary battery can be sufficiently improved. In this specification, the "number average particle size" of the inorganic solid electrolyte and the electrode active material can be determined by observing 100 particles of the inorganic solid electrolyte and the electrode active material using an electron microscope, measuring the particle size according to JIS Z8827-1:2008, and calculating the average value.

[0053] <<Polymer inorganic solid electrolyte>> Examples of polymeric inorganic solid electrolytes include polyethylene oxide derivatives and polymers containing polyethylene oxide derivatives, polypropylene oxide derivatives and polymers containing polypropylene oxide derivatives, phosphate polymers, and polycarbonate derivatives and polymers containing polycarbonate derivatives, which contain an electrolyte salt.

[0054] When the all-solid-state secondary battery is an all-solid-state lithium ion secondary battery, the electrolyte salt is not particularly limited, and examples thereof include fluorine-containing lithium salts such as lithium hexafluorophosphate (LiPF), lithium tetrafluoroborate (LiBF), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0055] <Electrode active material> The electrode active material is a material that transfers electrons at the electrode of an all-solid-state secondary battery. When the all-solid-state secondary battery is an all-solid-state lithium ion secondary battery, a material that can absorb and release lithium is usually used as the electrode active material. Hereinafter, a case will be described in which the all-solid-state secondary battery is an all-solid-state lithium ion secondary battery, but the present invention is not limited thereto.

[0056] The positive electrode active material is not particularly limited, and examples thereof include a positive electrode active material made of an inorganic compound and a positive electrode active material made of an organic compound. The positive electrode active material may be one type or a combination of two or more types in any ratio, and may be a mixture of an inorganic compound and an organic compound.

[0057] Examples of the positive electrode active material made of an inorganic compound include transition metal oxides, composite oxides of lithium and transition metals (lithium-containing composite metal oxides), transition metal sulfides, etc. Examples of the transition metals include Fe, Co, Ni, Mn, etc. Examples of the inorganic compounds used in the positive electrode active material include lithium-containing composite metal oxides such as Co-Ni-Mn (Li(Co Mn Ni)O2), Ni-Co-Al lithium-containing composite metal oxides, lithium-containing cobalt oxide (LiCoO2), lithium-containing nickel oxide (LiNiO2), lithium manganate (LiMnO2, LiMn2O4), olivine-type lithium iron phosphate (LiFePO4), and LiFeVO4; transition metal sulfides such as TiS2, TiS3, and amorphous MoS2; Cu2V2O3, amorphous V2O-P2O5, MoO3, V2O5, and V6O 13 and the like. These compounds may be partially element-substituted.

[0058] Examples of the positive electrode active material made of an organic compound include polyaniline, polypyrrole, polyacene, disulfide-based compounds, polysulfide-based compounds, and N-fluoropyridinium salts.

[0059] Examples of the negative electrode active material include carbon allotropes such as graphite and coke. The negative electrode active material made of a carbon allotrope can be in the form of a mixture or coating with a metal, metal salt, oxide, etc. Examples of the negative electrode active material include oxides or sulfates of silicon, tin, zinc, manganese, iron, nickel, etc.; metallic lithium; lithium alloys such as Li-Al, Li-Bi-Cd, and Li-Sn-Cd; lithium transition metal nitrides; silicone; and the like.

[0060] The number-average particle diameter of the electrode active material is preferably 0.1 μm or more, more preferably 1 μm or more, and is preferably 40 μm or less, more preferably 30 μm or less. If it is equal to or greater than the lower limit, handling is easy and the adhesiveness of the resulting electrode mixture layer can be sufficiently improved. On the other hand, if it is equal to or less than the upper limit, the surface area of ​​the electrode active material can be sufficiently secured, and the output characteristics of the all-solid-state secondary battery can be sufficiently improved.

[0061] <Other ingredients> In addition to the above components, the slurry composition of the present invention may contain components such as a leveling agent, a reinforcing agent, an antifoaming agent, an antiaging agent, a surfactant, a dispersant, etc. As these components, known ones may be used. The slurry composition of the present invention may contain a solvent that is optionally added during preparation of the slurry composition. The added solvent is not particularly limited, but is preferably an organic solvent listed for the conductive material paste. When an organic solvent is added, it is preferable that the organic solvent contained in the conductive material paste and the added organic solvent are the same in terms of compatibility. In addition, the slurry composition of the present invention may contain a binder component that is added at the time of preparing the slurry composition. The binder component to be added is not particularly limited, but is preferably the (meth)acrylic polymer mentioned in relation to the conductive material paste. When a (meth)acrylic polymer is added, it is preferable that the (meth)acrylic polymer contained in the conductive material paste and the (meth)acrylic polymer to be added are the same from the viewpoint of compatibility.

[0062] <Composition and viscosity of slurry composition> The amount of solid electrolyte contained in the slurry composition of the present invention is preferably such that the ratio of the solid electrolyte to the total amount (100 mass%) of the electrode active material and the solid electrolyte is 10 mass% or more, more preferably 20 mass% or more, and also preferably 70 mass% or less, more preferably 60 mass% or less. If it is equal to or more than the lower limit, the ion conductivity can be sufficiently ensured, the electrode active material can be effectively utilized, and the capacity of the all-solid-state secondary battery can be sufficiently increased. Also, if it is equal to or less than the upper limit, the amount of the electrode active material can be sufficiently ensured, and the capacity of the all-solid-state secondary battery can be sufficiently increased.

[0063] The amount of the conductive paste contained in the slurry composition of the present invention is preferably an amount such that the conductive material in the conductive paste is 0.5 parts by mass or more, and more preferably 1.0 part by mass or more, relative to 100 parts by mass of the combined amount of the electrode active material and the solid electrolyte, and is preferably an amount such that the conductive material is 10 parts by mass or less, and more preferably 5 parts by mass or less.

[0064] The amount of the conductive material per 100 parts by mass of the solid content of the slurry composition can be 0.5 parts by mass or more, preferably 1 part by mass or more, and can be 10 parts by mass or less, preferably 5 parts by mass or less.

[0065] The viscosity of the slurry composition of the present invention (Brookfield B type viscometer, 60 rpm, 25°C) can be 8000 mPa·s or less. The viscosity is preferably 6000 mPa·s or less, more preferably 5000 mPa·s or less. From the viewpoint of stability over time, the viscosity is preferably 500 mPa·s or more, more preferably 1000 mPa·s or more.

[0066] <Method of preparing slurry composition> The method for preparing the slurry composition of the present invention is not particularly limited, and examples thereof include a method of mixing the above-mentioned conductive paste, solid electrolyte, electrode active material, any additional organic solvent, and any other components.

[0067] (Electrode for all-solid-state secondary battery) The electrode for an all-solid-state secondary battery of the present invention (hereinafter also referred to as "electrode") is formed using the slurry composition for an all-solid-state secondary battery electrode of the present invention. For example, the slurry composition is applied to the surface of a current collector to form a coating film, and then the formed coating film is dried to obtain an electrode comprising a current collector and an electrode mixture layer on the current collector.

[0068] <Current collector> The current collector is not particularly limited as long as it is a material that has electrical conductivity and is electrochemically durable. From the viewpoint of heat resistance, metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, and platinum are preferred, and among them, aluminum is particularly preferred for the positive electrode, and copper is particularly preferred for the negative electrode. The shape of the current collector is not particularly limited, and a sheet-like one with a thickness of about 0.001 mm to 0.5 mm is preferred. The current collector is preferably roughened in advance before use in order to increase the adhesive strength with the electrode mixture layer. The roughening method is not particularly limited, and examples thereof include mechanical polishing, electrolytic polishing, and chemical polishing. In the mechanical polishing method, abrasive cloth paper to which abrasive particles are fixed, grinding stone, emery buff, wire brush equipped with steel wire, etc., are used. In addition, an intermediate layer may be formed on the surface of the current collector in order to increase the adhesive strength and electrical conductivity between the current collector and the electrode mixture layer.

[0069] <Electrode composite layer> The electrode mixture layer can be formed using the slurry composition of the present invention, and is made of a dried product of the slurry composition of the present invention, and contains at least a solid electrolyte, an electrode active material, a conductive material, and a (meth)acrylic polymer.

[0070] <Method of manufacturing electrodes for all-solid-state secondary batteries> The method for forming the electrode is not particularly limited, and examples thereof include a method including a step of applying the slurry composition of the present invention onto a current collector (application step) and a step of drying the slurry composition applied onto the current collector to form an electrode composite layer (drying step).

[0071] <<Coating process>> The method for applying the slurry composition of the present invention onto the current collector is not particularly limited, and examples thereof include a doctor blade method, a dip method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, and brush coating. The amount of the slurry composition to be applied is not particularly limited, and can be appropriately set depending on the desired thickness of the electrode mixture layer, etc.

[0072] <<Drying process>> The method for drying the slurry composition on the current collector is not particularly limited, and examples thereof include drying with warm air, hot air or low-humidity air, vacuum drying, and drying by irradiation with (far) infrared rays or electron beams, etc. Drying conditions can be appropriately set, and the drying temperature is preferably 50° C. or higher and 250° C. or lower, and more preferably 80° C. or higher and 200° C. or lower. The drying time is not particularly limited, and is usually performed within a range of 10 minutes to 60 minutes. The electrode may be stabilized by pressing the dried electrode, which may be performed by, but is not limited to, a method such as die pressing or calendar pressing.

[0073] The weight of the electrode mixture layer is not particularly limited and may be up to 1.0 mg / cm 2 More preferably, it is 5.0 mg / cm or more. 2 or more, and 30.0 mg / cm 2 Less than 25.0 mg / cm is preferred. 2 The following is more preferred:

[0074] (All-solid-state secondary battery) The all-solid-state secondary battery of the present invention includes the electrode of the present invention. That is, the all-solid-state secondary battery of the present invention has at least one of a positive electrode and a negative electrode formed using a slurry composition for all-solid-state secondary battery electrodes that contains the conductive material paste of the present invention.

[0075] Here, the electrode that can be used in the all-solid-state secondary battery of the present invention and does not fall under the electrode of the present invention is not particularly limited, and any electrode for an all-solid-state secondary battery can be used.

[0076] In addition, the solid electrolyte layer that can be used in the all-solid-state secondary battery of the present invention is not particularly limited, and any solid electrolyte layer can be used.

[0077] The all-solid-state secondary battery of the present invention can be obtained by laminating a positive electrode and a negative electrode so that the positive electrode composite layer of the positive electrode and the negative electrode composite layer of the negative electrode face each other via a solid electrolyte layer, optionally applying pressure to obtain a laminate, and then placing the laminate in a battery container as is or after rolling or folding, etc., depending on the shape of the battery, and sealing the battery container. If necessary, an expand metal, a fuse, an overcurrent prevention element such as a PTC element, a lead plate, etc. can be placed in the battery container to prevent pressure rise inside the battery and overcharging and discharging. The shape of the battery is not particularly limited, and examples thereof include coin type, button type, sheet type, cylindrical type, square type, flat type, etc. EXAMPLES

[0078] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the following, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In the examples and comparative examples, the content ratio of the monomer unit of the polymer, the weight average molecular weight, and the gel amount were measured as follows. The solubility parameter was the value calculated by the Hansen solubility parameter (unit: (cal / cm 3 ) 1 / 2 The dispersibility of the conductive paste and the battery characteristics (internal resistance, high-temperature cycle characteristics) of the all-solid-state secondary battery were evaluated as follows.

[0079] <Content of monomer units in polymer> 100 g of the binder solution prepared in Example 8 described later was solidified with 1 L of methanol, and then vacuum dried at a temperature of 60° C. for 12 hours. The obtained dried polymer was 1 The results were analyzed by H-NMR. Based on the analytical values ​​obtained, the content (mass%) of each monomer unit contained in the polymer in the binder solution was calculated. The content ratios of the monomer units in the other examples and comparative examples are substantially the same as the content ratios (charged amounts) of each monomer in the monomer composition.

[0080] <Weight average molecular weight of polymer> The weight average molecular weight of the polymer prepared in each Example and Comparative Example was calculated based on the polystyrene equivalent molecular weight obtained using high performance liquid chromatography (apparatus: Tosoh Corporation, model number "HLC8220"). For high performance liquid chromatography, three columns connected together (Showa Denko KK, model number "Shodex KF-404HQ", column temperature: 40°C, carrier: tetrahydrofuran with a flow rate of 0.35 ml / min) and a differential refractometer and an ultraviolet detector were used as detectors. The molecular weight was calibrated at 12 points using standard polystyrene (Polymer Laboratory Co., Ltd., standard molecular weight: 500 to 3,000,000).

[0081] <Gel amount (THF insoluble amount)> In the preparation of the binder solution of each Example and Comparative Example, the aqueous dispersion after polymerization of the monomer (in Example 8, the aqueous dispersion of the (meth)acrylic polymer concentrated after the hydrogenation reaction) was dried under an environment of 50% humidity and 23°C to 25°C to prepare a film having a thickness of 3±0.3 mm. The prepared film was cut into 5 mm squares to prepare a plurality of film pieces, and about 1 g of these film pieces was precisely weighed. The weight of the precisely weighed film piece was defined as W0. Next, the precisely weighed film piece was immersed in 100 g of tetrahydrofuran (THF) at 25°C for 24 hours. Thereafter, the film piece was pulled out from the THF, and the pulled out film piece was vacuum dried at 105°C for 3 hours, and its weight (weight of the insoluble portion) W1 was measured. Then, the THF insoluble portion (%) was calculated according to the following formula, and was defined as the gel amount (mass%). Gel amount (mass%) = W1 / W0 x 100

[0082] <Dispersibility of conductive paste> The conductive paste prepared in each of the Examples and Comparative Examples was stirred three times at 2000 rpm for 1 minute using a planetary centrifugal mixer (Awatori Rentaro ARE310), and then measured with a Brookfield B-type viscometer (60 rpm, 25°C, spindle shape 64). A: Viscosity 1000 mPa s or more but less than 3000 mPa s B: Viscosity 3000 mPa·s or more but less than 5000 mPa·s C: Viscosity 5000 mPa·s or more but less than 8000 mPa·s D: Viscosity 8000 mPa·s or more or no dispersion (no fluidity)

[0083] <Battery characteristics (internal resistance: IV resistance)> The all-solid-state secondary batteries produced in the examples and comparative examples were charged to 50% of SOC (State Of Charge, charge depth) at 1C (C is a value expressed as rated capacity (mA) / 1h (hours)) in a 25°C atmosphere, and then charged for 30 seconds and discharged for 30 seconds at 0.5C, 1.0C, 2.0C, and 5.0C, centered on 50% SOC. The battery voltage after 30 seconds in each case (charging side and discharging side) was plotted against the current value, and the slope was calculated as IV resistance (Ω) (IV resistance during charging and IV resistance during discharging). The obtained IV resistance value (Ω) was evaluated according to the following criteria. The smaller the IV resistance value, the lower the internal resistance. A: IV resistance 80Ω or less B: IV resistance more than 80Ω and less than 90Ω C:IV resistance more than 90Ω and less than 100Ω D:IV resistance over 100Ω

[0084] <Battery characteristics (high temperature cycle characteristics)> The all-solid-state secondary batteries produced in the Examples and Comparative Examples were charged at 60° C. from 3 V to 4.3 V at 0.1 C, and then discharged at 0.1 C from 4.3 V to 3 V, and this cycle was repeated for 100 cycles. The capacity retention rate, expressed as the ratio (d / c (%)) of the 0.1 C discharge capacity d at the 100th cycle to the 0.1 C discharge capacity c at the 5th cycle, was determined and used as the evaluation standard for high-temperature cycle characteristics, which were evaluated according to the following criteria. The larger this value, the smaller the discharge capacity loss and the more excellent the high-temperature cycle characteristics. A: Capacity retention rate of 60% or more B: Capacity retention rate: 50% to less than 60% C: Capacity retention rate: 40% to less than 50% D: Capacity retention rate: 30% to less than 40%

[0085] Example 1 <Preparation of (meth)acrylic polymer and binder solution> In a 1 L flask equipped with a stirrer and a septum, 100 parts of ion-exchanged water and 0.2 parts of sodium dodecylbenzenesulfonate as an emulsifier were added, the gas phase was replaced with nitrogen gas, and the temperature was raised to 60°C. After that, 0.25 parts of potassium persulfate (KPS) was dissolved in 20.0 parts of ion-exchanged water as a polymerization initiator and added. Meanwhile, in a separate container, 40 parts of ion-exchanged water, 1.0 part of sodium dodecylbenzenesulfonate as an emulsifier, 15 parts of styrene (St), 80 parts of n-butyl acrylate (BA), and 5 parts of acrylonitrile (AN) were mixed to obtain a monomer composition. This monomer composition was continuously added to the 1 L flask with a septum over a period of 3 hours to carry out polymerization. During the addition, the reaction was carried out at 60°C. After the addition was completed, the mixture was stirred at 80°C for an additional 3 hours to terminate the reaction. Next, an appropriate amount of an organic solvent (butyl butyrate) was added to the obtained aqueous dispersion of the polymer to obtain a mixture, which was then distilled under reduced pressure at 90°C to remove water and excess butyl butyrate from the mixture to obtain a binder solution (solid concentration: 8%).

[0086] <Preparation of conductive paste> The above binder solution (equivalent to 1 part of solid content) and acetylene black (Denka Black Powder: Denki Kagaku Kogyo, specific surface area 68 m) as a conductive material were 2 3 parts of ethylenediaminetetraacetate (1.0 parts / g, average particle size 35 nm) were mixed, and butyl butyrate was added to the resulting mixture to prepare a composition with a solid content concentration of 10%. This composition was mixed in a planetary mixer to obtain a conductive material paste. The resulting conductive material paste was used to evaluate dispersibility.

[0087] <Preparation of Slurry Composition for Negative Electrode Mixture Layer> 65 parts of graphite (number average particle diameter: 20 μm) as a negative electrode active material, 30 parts of sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle diameter: 0.9 μm) consisting of Li2S and P2S5 as an inorganic solid electrolyte, the conductive paste (equivalent to 3 parts of acetylene black), and the binder solution (equivalent to 1 part of solid content) were mixed, and butyl butyrate was added to the resulting mixture to prepare a composition with a solid content concentration of 60%. This composition was mixed with a planetary mixer to obtain a slurry composition for a negative electrode composite layer.

[0088] <Preparation of Slurry Composition for Positive Electrode Mixture Layer> The positive electrode active material is a lithium composite oxide of Co-Ni-Mn, NMC532 (LiNi 5 / 10 Co 2 / 10 Mn 3 / 10 100 parts of 100% 1,024-tetrafluoroethylene (10.0 μm), 50 parts of sulfide glass (Li2S / P2S5=70 mol% / 30 mol%, number average particle diameter: 0.4 μm) consisting of Li2S and P2S5 as a solid electrolyte, 3 parts of acetylene black as a conductive material, and the above binder solution (equivalent to 2 parts solid content) were mixed, and butyl butyrate was added to the resulting mixture to prepare a composition with a solid content concentration of 75%. This composition was mixed in a rotation / revolution mixer and further adjusted to a solid content concentration of 70% with butyl butyrate to obtain a slurry composition for a positive electrode composite layer.

[0089] <Preparation of Slurry Composition for Solid Electrolyte Layer> 98 parts of sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle size: 0.9μm) consisting of Li2S and P2S5 as a solid electrolyte was mixed with the above binder solution (equivalent to 2 parts solid content), and butyl butyrate was added to the resulting mixture to prepare a composition with a solid content concentration of 60%. This composition was mixed with a planetary mixer to obtain a slurry composition for a solid electrolyte layer.

[0090] <Preparation of negative electrode> The above-mentioned slurry composition for the negative electrode composite layer was applied to the surface of a copper foil as a current collector, and dried at 120° C. for 30 minutes to form a negative electrode composite layer (basis weight: 10.0 mg / cm) on one side of the copper foil as a current collector. 2 ) was obtained.

[0091] <Preparation of positive electrode> The slurry composition for the positive electrode mixture layer was applied to the surface of an aluminum foil as a current collector, and dried at 120° C. for 30 minutes to form a positive electrode mixture layer (basis weight: 18.0 mg / cm) on one side of the aluminum foil as a current collector. 2 ) was obtained.

[0092] <Preparation of solid electrolyte layer> The slurry composition for the solid electrolyte layer was dried on a release sheet as a substrate, and the dried material peeled off from the release sheet was ground in a mortar to obtain a powder. 0.05 mg of the obtained powder was placed in a 10 mmφ mold and molded under a pressure of 200 MPa to obtain a pellet (solid electrolyte layer) with a thickness of 500 μm.

[0093] <Production of all-solid-state secondary batteries> The negative electrode and positive electrode obtained as described above were each punched out to a diameter of 10 mm. The solid electrolyte layer obtained as described above was sandwiched between the punched positive electrode and negative electrode (in this case, the electrode mixture layer of each electrode was in contact with the solid electrolyte layer), and pressed at a pressure of 200 MPa to obtain a laminate for an all-solid-state secondary battery. The obtained laminate was placed in an evaluation cell (confining pressure: 40 MPa) to obtain an all-solid-state secondary battery. The cell characteristics of the obtained all-solid-state secondary battery were evaluated. The results are shown in Table 1.

[0094] In Examples 1 to 7, 9 to 10 and Comparative Examples 2 to 5, conductive material pastes, slurry compositions for negative electrode composite layers, slurry compositions for positive electrode composite layers, slurry compositions for solid electrolyte layers, negative electrodes, positive electrodes, and all-solid-state secondary batteries were manufactured in the same manner as in Example 1. However, the types and amounts of the monomers in the monomer compositions and the types of the solvents were changed to the types and amounts shown in Table 1. The solvents used in the slurry compositions for negative electrode composite layers, the slurry compositions for positive electrode composite layers, and the slurry compositions for solid electrolyte layers were the same as the solvents used in the conductive material pastes of each Example and Comparative Example (the same organic solvents used in the preparation of the binder solutions of each Example and Comparative Example, as shown in Table 1). The obtained conductive material pastes and all-solid-state secondary batteries were evaluated for dispersibility and cell characteristics of the batteries. The results are shown in Table 1.

[0095] Example 8 A conductive material paste, a slurry composition for a negative electrode composite layer, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a solid electrolyte layer, a negative electrode, a positive electrode, and an all-solid-state secondary battery were produced in the same manner as in Example 1, except that a (meth)acrylic polymer was prepared as follows, and a binder solution was obtained. The conductive material paste and the all-solid-state battery obtained were evaluated for dispersibility and cell characteristics of the battery. The method for measuring the content ratio of the monomer unit in the (meth)acrylic polymer is as described above.

[0096] A reactor was charged with 2 parts of potassium oleate as an emulsifier, 0.1 parts of potassium phosphate as a stabilizer, and 150 parts of water, and further added with 19 parts of acrylonitrile, 48 parts of 1,3-butadiene, 33 parts of butyl acrylate (BA), and 0.31 parts of t-dodecyl mercaptan as a molecular weight regulator, and emulsion polymerization was initiated at 10° C. in the presence of 0.015 parts of ferrous sulfate as an activator and 0.05 parts of paramenthane hydroperoxide as a polymerization initiator. When the polymerization conversion rate reached 85%, 0.2 parts of hydroxylamine sulfate per 100 parts of monomer was added to terminate the polymerization. Following termination of the polymerization, the mixture was heated and subjected to steam distillation under reduced pressure at 70° C. to recover unreacted monomers, after which 2 parts of alkylated phenol were added as an antioxidant to obtain an aqueous dispersion of the polymer.

[0097] 400mL of the aqueous dispersion of the obtained polymer (total solid content: 48g) was placed in a 1-liter autoclave equipped with a stirrer, and nitrogen gas was passed through for 10 minutes to remove dissolved oxygen in the aqueous dispersion. Then, 50mg of palladium acetate was dissolved in 180mL of water containing 4 times the molar amount of nitric acid relative to Pd as a hydrogenation reaction catalyst and added. After replacing the inside of the system with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3MPa, and hydrogenation reaction was carried out for 6 hours. The contents were returned to room temperature, the inside of the system was conditioned with nitrogen, and the contents were then concentrated using an evaporator until the solid concentration reached 40%, to obtain an aqueous dispersion of a (meth)acrylic polymer. Next, an appropriate amount of butyl butyrate was added to the obtained aqueous dispersion of the (meth)acrylic polymer to obtain a mixture, which was then distilled under reduced pressure at 90°C to remove water and excess butyl butyrate from the mixture to obtain a binder solution (solid concentration: 8%).

[0098] Comparative Example 1 As described below, except that the slurry composition for the negative electrode composite layer was prepared without using a conductive material paste, a slurry composition for the positive electrode composite layer, a slurry composition for the solid electrolyte layer, a solid electrolyte layer, a negative electrode, a positive electrode, and an all-solid-state secondary battery were produced in the same manner as in Example 1, and the cell characteristics of the battery were evaluated. The results are shown in Table 1.

[0099] <Preparation of Slurry Composition for Negative Electrode Mixture Layer> 100 parts of graphite (number average particle diameter: 20 μm) as a negative electrode active material, 50 parts of sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle diameter: 0.4 μm) consisting of Li2S and P2S5 as a solid electrolyte, and the binder solution (equivalent to 3 parts solid content) prepared in Example 1 were mixed, and butyl butyrate was added to the resulting mixture to prepare a composition with a solid content concentration of 65%. This composition was mixed in a rotation / revolution mixer and further adjusted to a solid content concentration of 60% with butyl butyrate to obtain a slurry composition for a negative electrode composite layer.

[0100] Example 11 A slurry composition for a negative electrode composite layer and a slurry composition for a positive electrode composite layer were prepared as follows. The slurry composition for a positive electrode composite layer contains the conductive paste of the present invention. Otherwise, a slurry composition for a solid electrolyte layer, a solid electrolyte layer, a positive electrode, a negative electrode, and an all-solid secondary battery were prepared in the same manner as in Example 1, and the cell characteristics of the battery were evaluated. The results are shown in Table 1.

[0101] <Preparation of Slurry Composition for Negative Electrode Mixture Layer> 100 parts of graphite (number average particle diameter: 20 μm) as a negative electrode active material, 50 parts of sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle diameter: 0.4 μm) consisting of Li2S and P2S5 as a solid electrolyte, and the binder solution (equivalent to 3 parts solid content) prepared in Example 1 were mixed, and butyl butyrate was added to the resulting mixture to prepare a composition with a solid content concentration of 65%. This composition was mixed in a rotation / revolution mixer and further adjusted to a solid content concentration of 60% with butyl butyrate to obtain a slurry composition for a negative electrode composite layer.

[0102] <Preparation of Slurry Composition for Positive Electrode Mixture Layer> The positive electrode active material is a lithium composite oxide of Co-Ni-Mn, NMC532 (LiNi 5 / 10 Co 2 / 10 Mn 3 / 1065 parts of 10.0 μm of Li2S and P2S5 sulfide glass (Li2S / P2S5=70 mol% / 30 mol%, number average particle diameter: 0.9 μm) as an inorganic solid electrolyte, 30 parts of the conductive paste (equivalent to 3 parts of acetylene black) prepared in Example 1, and the binder solution (equivalent to 1 part of solid content) prepared in Example 1 were mixed, and butyl butyrate was added to the resulting mixture to prepare a composition with a solid content concentration of 75%. This composition was mixed for 60 minutes with a planetary mixer, and further adjusted to a solid content concentration of 70% with butyl butyrate, and then mixed for 10 minutes with a planetary mixer to obtain a slurry composition for a positive electrode composite layer.

[0103] [Table 1]

[0104] In Examples 1 to 11, in which the conductive paste of the present invention was used, all-solid-state secondary batteries having sufficiently reduced internal resistance and excellent high-temperature cycle characteristics were obtained. It was also confirmed that the dispersibility of the conductive material in each conductive paste was good. In Comparative Example 1, in which a slurry composition prepared without using a conductive material paste was used, the internal resistance of the obtained all-solid-state secondary battery was not sufficiently reduced, and the high-temperature cycle characteristics were also poor. In addition, in Comparative Examples 2 to 5, a conductive material paste was used, but either the binder component or the organic solvent was outside the range of the present invention, and the internal resistance of the obtained all-solid-state secondary battery was not sufficiently reduced, and the high-temperature cycle characteristics were also poor.

Claims

1. A conductive material, a polymer containing 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units and α,β-unsaturated nitrile monomer units and having a gel content of 50% by mass or less, and a solubility parameter (SP value) of 6.4 (cal / cm 3 ) 1/2 More than 10.0 (cal / cm 3 ) 1/2 A conductive material paste for an electrode of an all-solid-state secondary battery, comprising the following organic solvent:

2. The conductive paste for an all-solid-state secondary battery electrode according to claim 1, wherein the content of the α,β-unsaturated nitrile monomer unit in the polymer is 2% by mass or more and 30% by mass or less.

3. The conductive paste for an all-solid-state secondary battery electrode according to claim 1 or 2, wherein the polymer contains a hydrophobic monomer unit.

4. The conductive paste for an all-solid-state secondary battery electrode according to claim 3 , wherein the content of the hydrophobic monomer unit in the polymer is 3% by mass or more and 60% by mass or less.

5. A slurry composition for an all-solid-state secondary battery electrode, comprising the conductive paste for an all-solid-state secondary battery electrode according to any one of claims 1 to 4, a solid electrolyte, and an electrode active material.

6. An electrode for an all-solid-state secondary battery, comprising an electrode mixture layer formed using the slurry composition for an all-solid-state secondary battery electrode according to claim 5.

7. An all-solid-state secondary battery comprising the electrode for an all-solid-state secondary battery according to claim 6.

Citation Information

Patent Citations

  • Conductive material dispersion liquid, electrode paste, and conductive material coating active substance

    JP2011070908A

  • Carbon black dispersion and use of the same

    JP2015229716A

  • Positive electrode mixture manufacturing method, positive electrode manufacturing method, all-solid lithium ion secondary battery manufacturing method, positive electrode mixture, positive electrode, and all-solid lithium ion secondary battery

    JP2017147158A

  • Fabrication method electrode for all-solid-state battery

    KR1020170050234A

  • Electrode for all-solid-state secondary batteries and method for producing same

    WO2013146916A1